The in vitro and in vivo biological activities of antifungal compounds isolated from Loxostylis alata A.Spreng. ex Rchb. leaf extracts - Naidoo, Vinny (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.